19.2: Distinguished Paper: Characterization of Electron‐Hole Pair Migration and Trapping in Rare Earth Doped YBO3 under Vacuum Ultraviolet Excitation. Issue 1 (1st July 2013) - Wallace, Max; Diaz, Anthony L.
Abstract We have measured host‐to‐activator energy transfer efficiencies in rare‐earth doped YBO3 under vacuum ultraviolet excitation. From these data, relative electron‐hole (e‐h) pair trapping rate constants can be estimated. Our analysis suggests a correlation between e‐h trapping efficiency and the energy of activator electronic states relative to the host conduction band.